Strategies for Developing Public Speaking Skills in Arabic for Students of the Pondok Pesantren Al-Itqon Kendal / إستراتيجيات تطوير مهارة الخطابة العامة باللغة العربية لدى طلبة معهد الإتقان الإسلامي كندال - Muhammad Fahrun Nadhif; M. ‘Athif Audl Ramadlan (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2024)
Pondok Pesantren Al-Itqon Kendal has developed programs to enhance the Arabic public speaking skills of its students, which include three main programs: regular Arabic speech, speech writing (Insya’), and spontaneous speaking practice (Muhadatsah). These programs are designed to enhance students’ communication abilities, not only in public speaking but also in building character, self-confidence, and mental preparedness. Through varied tasks, students are given the opportunity to act as emcees, speakers, or keynote speakers, all conducted in Arabic. Additionally, each program is complemented by constructive feedback from supervisors and teachers to improve strengths and weaknesses in speaking. The results show that the program successfully addresses the overcoming public speaking anxiety, improves delivery techniques, and strengthens leadership and social skills. Furthermore, social learning theory and experiential learning provide a strong foundation for this skill development, where observation, imitation, and repeated practice play a key role in enhancing speaking abilities in front of an audience. Overall, this public speaking program contributes significantly to character development and social skills, preparing students to become ambassadors of knowledge and religious values in society.